THE NEED FOR A DIGITAL MODULE TO IMPROVE THE NUMERICAL LITERACY OF DYSCALCULIA STUDENTS - Jayanti Putri Purwaningrum; Latifah Nur Ahyani; Andi Prasetyo Utomo (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2022)
Numerical literacy is the ability to collaborate understanding and knowledge of mathematics effectively in facing life's challenges. This ability is very important for every student to solve everyday problems, including dyscalculia students (having difficulty learning mathematics). This research is a qualitative descriptive describing the need for a digital-based module to improve the numerical literacy of dyscalculia students. The digital-based module is an application to be used anytime and anywhere. The subjects of this study were six teachers and 18 students with dyscalculia, a combination of six primary schools in Kudus Regency, Central Java, Indonesia. The instruments used in this study were interview sheets, observation sheets, and questionnaires for a digital module need. Students were classified as dyscalculia based the dyscalculia screening test and the WISC (Wechsler Intelligence Scale for Children) test. The data analysis involved data reduction, data presentation, and concluding. This study indicates that a digital module is needed by teachers to improve the numerical literacy of elementary school students, especially students with dyscalculia. The development of a digital module can increase students’ motivation and interest in studying abstract mathematical concepts.